Formulation and physical stability test of oleanolic acid cream and gel - Kartini, Kartini; Fitriani, Endang Wahyu; Tansridjata, Laurances (Pharmaciana, 2018)
Plantago major has been empirically used for wound healing. One of its chemical compounds, oleanolic acid, exhibited wound healing activity on hyperglycemic rats. The aims of this study were to (1) formulate oleanolic acid into topical dosage forms i.e. cream and gel; and (2) evaluate the physical stability of the products. Oleanolic acid was formulated into the dosage forms using stearic acid, isopropyl palmitate and cetyl alcohol as the cream base and carbomer as the gel base. Cream and gel were then subjected into accelerated (40±2°C/75±5% RH) and room temperature (27±2°C/73±5% RH) stability test for six weeks. Physical stability was determined using parameters of visual appearance, specific gravity, viscosity and flow properties, for both gel and cream, as well as the type of emulsion and particle size for the cream. Data analysis were performed using one-way ANOVA and paired t-test. It is concluded that gel and cream of oleanolic acid were able to maintain their visual appearance, specific gravity, viscosity and flow properties during six weeks of storage. In addition, oleanolic acid cream could also maintain its particle size and type of emulsion during testing.